(untitled) (Comprehensive Journal of Science, 2026)
This study examines the influence of dark patterns versus ethical design in AI-driven recommendation systems on consumer choice, trust, and loyalty in e-commerce environments. The study is motivated by the increasing adoption of AI recommendation systems and the growing ethical concerns associated with persuasive and manipulative interface practices. A descriptive analytical approach was adopted, and data were collected through an online questionnaire with 35 valid responses. The questionnaire measured four main constructs: dark patterns, ethical design, consumer trust, and loyalty. The descriptive results show that dark patterns achieved a moderate overall mean of 3.41, indicating that practices such as false scarcity messages and countdown timers can influence purchase decisions. Ethical design achieved a higher mean of 3.84, while consumer trust recorded 3.77 and loyalty achieved the highest mean of 4.13. Reliability analysis showed strong internal consistency, with an overall Cronbach’s alpha of 0.913. The findings suggest that while dark patterns may generate short-term behavioral influence, ethical design appears to be more sustainable in strengthening consumer trust and long-term loyalty. The study recommends that e-commerce platforms adopt transparent, explainable, and user-centered AI recommendation practices and reduce manipulative interface strategies that undermine consumer autonomy.